The analysis of assessment instruments in English teacher lesson plans at junior high school in Singaraja Bali - Desak Ketut Indriyani; Luh Putu Artini; Luh Diah Surya Adnyani (Journal of Research on English and Language Learning (J-REaLL), 2021)
Education and Culture Ministry Regulation 81A Year 2013 has demanded teachers to use authentic assessment as a method of assessing students’ competences which is applied in English teachers’ lesson plans. This research aims to describe types of assessment instruments used in lesson plans, the relevancy between the assessments and indicators in the lesson plans, and the authenticity of assessment instruments used by English teachers as demanded by Curriculum 2013. The data were collected through document analysis of 20 English teachers' lesson plans from 4 Junior High Schools in Singaraja, Bali. The research model from Miles and Huberman (1984) was adopted in data analysis process. The instruments were derived and modified from principles of authentic assessment in Education and Culture Ministry Regulation 81A Year 2013. As the result, it was found that performance assessments and project assessment were used as the assessment types in the implementation of authentic assessment. The assessment instruments were relevant to the indicator of learning and the skills’ aspects in assessment instruments used was authentic as demanded byCurriculum 2013.